HUBUNGAN ASUPAN PROTEIN, KONSUMSI SUPLEMEN, DAN IMT/U DENGAN TINGKAT KEBUGARAN JASMANI PADA ATLET CABANG OLAHRAGA PERMAINAN DI SMA RAGUNAN JAKARTA - Zilca Zalfaneswari, (2021)
The prevalence of physical fitness in PPOP DKI Jakarta Province in 2020 in athletes in sports games only 21% good category. Physical fitness in a good category increase the health degress which is influenced by several factors: age, gender, protein intake, supplements consumption, and BMI/U. This study aims to find out the relationship between protein intake, supplement consumption, and BMI/U with physical fitness levels in athletes in sports games at SMA Ragunan Jakarta. This study used cross-sectional design with sampling techniques, namely purposive sampling on 53 athletes aged 15-18 years at SMA Ragunan Jakarta. Retrieval and collection of protein intake data by 2x24-hour food recall method, consumption of supplements with questionnaires, and BMI/U data with secondary data. The data obtained was tested using the pearson correlation test. The results showed that protein intake (p=0.004) and BMI/U (p=0.000) had a relationship (p<0.05) with athletes' physical fitness levels. Meanwhile, supplement consumption (p=0.313) had no relationship (p<0.05) to the athlete's physical fitness level.